P303 Exploring the role of shift work in population-based prospective cohort studies of cancer. (1st September 2016) - Carreón, Tania; Robinson, Susan; DeBono, Nathaniel; MacDonald, Leslie; Pinkerton, Lynne
Abstract : Epidemiologic evidence in humans for a link between shift work and cancer remains inconclusive, despite renewed interest in the subject subsequent to the International Agency for Research on Cancer classification of shift work involving circadian rhythm disruption as a probable carcinogen (group 2A) in 2007. In this study, we reviewed ongoing or recently completed population-based prospective cohort studies of cancer risk factors in adults to evaluate the data collected on occupation, including work schedules and shift work, and the use of these data in the assessment of cancer risk. We also recorded information collected on lifestyle factors that may be associated with cancer or modify risks associated with shift work. Fifty-three cohorts were identified using the National Cancer Institute Cohort Consortium Membership list, pooled studies that used prospective population-based cohorts, and a NIH RePORTER database search. Publications with cancer-specific outcomes were identified using publication lists on cohort websites, searches in journal databases such as PubMed and Scopus, and citation tracking from previously found publications. Questionnaires from 45 cohorts and 3, 393 publications that met inclusion criteria were reviewed; principal investigators of each cohort were contacted to corroborate the information abstracted. Twenty-four cohorts collected occupational histories and thirteen have obtained information on shift work, including duration (77%), intensity (46%), and rotating shift schedules (85%). Eighteen publications from six cohorts have investigated associations between shift work and breast, ovarian, uterine, lung, colorectal, prostate, or pancreatic cancers. Relatively few reviewed studies have investigated the relationship between shift work and cancer. We are exploring opportunities to collaborate in studies by analysing existing data or by collecting information on occupation, work schedules, and shift work in studies that are still following up study participants, to further scientific knowledge of the role of shift work in cancer.